(3eHGOF GdJMdjd GdGbJUGO Gdcdj eY JeGQjf h eSGFd eMdhdI (B/s - (3Jhej, UGdMs ((3GdLRGFQ(B: s (3OGQ GSGeI(B, s, 2009)
(3eONd deaghe GdGbJUGO Gdcdj h dMSGHGJ GdONd GdhWfj , GdfehPL GdcdGSjcj GdCSGSj ddYeGdI , GdfbhO , GdCSYGQ h SYQ GdaGFOI ,GdfehPL GdcjfRj GdHSjW ddONd h GdGfaGb , OhQ GdfbhO , GdaGFOI ,SYQ GdUQa h GdONd aj JMOjO GdeSJhi GdJhGRfj ddfGJL , GdJPHPHGJ GdGbJUGOjI aj GdCLdjf GdbUjQ h GdWhjd h YdGbJgG HGdfGJL , GdGSYGQ h GdYeGdI , OjfGejcjI GdJVNe h GdHWGdI eY hLhO SdSdI JeGQjf eMdhdI h ZjQ eMdhdI aj fgGjI cd aUd (B.s
(3eQGLY U(B.429(3;ghGeT U(B.420s
Keywords: (3GdGbJUGO Gdcdjs; (3GdHWGdIs; (3GdJMdjd GdGbJUGOjs; (3GdJMdjd GdGbJUGOj Gdcdjs; (3GdJVNes